EFFECT OF PRICE , PRODUCT AND CONSUMER PURCHASE DECISION AGAINST LOCATION IN INDAH GROUP SWALAYAN LUBUK BASUNG - Afandi, ãDesmar Rodian; Sari, Mareta Kemala; Hidayat, Rian (Pendidikan Ekonomi, 2014)
ABSTRACTThis study aimed to determine the effect of price , product and location on consumer purchasing decisions in Belle Group Self Lubuk cone . This type of research is quantitative . The method used in this research is descriptive method associative . The study population was all consumers who shop at Belle Group Self Lubuk cone . The study sample was taken by means of nonprobability sampling ( non- probability sampling ) is a sampling technique that does not provide the opportunity / equal opportunity for each element or selected members of the population to be sampled . Based on the theory Rosce Sekaran , a sample was taken of 100 respondents. Results of the study : 1 ) . Partially known price variables significantly influence consumer purchasing decisions Belle Group Self . This is evidenced by the results of research which states that tcount ( 4.675 ) > t table ( 1.66 ) and Sig ( 0,000 ) < α ( 0.05 ) , meaning that Ho1 was rejected Ha1 accepted . From the results of the regression coefficient of the regression test known price variable is positive 0.663 . 2 ) . Products positive and significant impact on consumer purchasing decisions Belle Group Self . This is evidenced by the results of research which states that the value of t ( 2.754 ) > t table ( 1.66 ) and Sig ( 0.007 ) < α ( 0.05 ) Ha2 acceptable means Ho2 rejected . From the results of the regression coefficient of the regression test known price variable is positive 0.239 . 3 ) . Location positive significant effect on consumer purchasing decisions Belle Group Self . This is evidenced by the results of research which states that the value of t ( 3.615 ) > t table ( 1.66 ) and Sig ( 0,000 ) < α ( 0.05 ) means HO3 rejected Ha3 accepted . From the results of the regression coefficient of the regression test known price variable is positive 0.523 .